Analysis of a multicriterial buffer capacity optimization problem for a production line - Dolgui, A. B.; Eremeev, A. V.; Sigaev, V. S. (Automation and remote control, 2017)
We consider a multicriterial optimization problem for volumes of buffers in a production line. We assume that the line has a series-parallel structure, and during its operation equipment stops occur due to failures, stops that are random in the moments when they arise and in their durations. The volumes of buffers are integer-valued and bounded from above. As criteria we consider the average production rate of the line, capital costs for installing buffers, and the inventory cost for intermediate products. To approximate the Pareto optimal set we use evolutionary algorithms SIBEA and SEMO. Problems with larger dimension experimentally support the advantage of the modified SEMO algorithm with respect to the hypervolume of the resulting set of points.